MATA BESAN: Edukasi Bebas Anemian Pada Mahasiswa di Masa Pandemi Covic-19 - Siregar, Mukhlidah Hanun; Zulfikar, Agnia Nafisa; Sijabat, Agnes Irma Yuliarta; Gultom, Yohana Septa; NurBarokah, Sopi; Hidayah, Rahmah Nur; Wiani, Uci Amelinda Akta (LPPM Universitas HKBP Nommensen, 2024)
Anaemia is a health problem that can occur in all age groups. One in 5 adults is anaemic, and 1 in 3 women of childbearing age is anaemic. This activity was named MATA BESAN, namely Anemia Free Tough Students, to educate anaemia prevention students in Banten Province. The implementation was done online and offline from May 27 until June 2, 2021, using video media, pamphlets, and a guidebook. The activity results showed increasing student knowledge scores from pre and post-test from an average of 67 to 88. This activity's online and offline methods have proven effective in reaching targets and increasing student knowledge. This activity is expected to prevent anaemia in Banten Province students by paying attention to broader socialization and more intensive and sustainable activities.